2015
DOI: 10.1177/0022034515578908
|View full text |Cite
|
Sign up to set email alerts
|

Dental Follicle Cells Participate in Tooth Eruption via the RUNX2-MiR-31-SATB2 Loop

Abstract: Cleidocranial dysplasia (CCD) is characterized by the runt-related transcription factor 2 (RUNX2) mutation, which results in delayed tooth eruption due to disturbed functions of dental follicle. Accumulating evidence has revealed a key regulatory circuit, including RUNX2, miR-31, and special AT-rich binding protein 2 (SATB2) acting in concert in mesenchymal stem cell homeostasis and functions. However, whether such a regulatory loop works in dental follicle cells (DFCs) remains unknown. Herein, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 27 publications
5
52
0
Order By: Relevance
“…The reduced protein levels of SATB2 suggested that expression of miR‐31a‐5p was negatively correlated with SATB2 levels. We used TargetScan to predict the target of miR‐31a‐5p and found that miR‐31a‐5p could bind to the 3′‐untranslated region (3′UTR) of SATB2 (Figure 3g), a pluripotency transcription factor, which has been previously demonstrated (Deng, Wu et al., 2013; Ge et al., 2015). To further demonstrate whether miR‐31a‐5p regulated osteogenesis via SATB2, the osteogenic capacity of si‐SATB2 treated BMSCs was rejuvenated by miR‐31a‐5p inhibition (Figure 3h,i).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced protein levels of SATB2 suggested that expression of miR‐31a‐5p was negatively correlated with SATB2 levels. We used TargetScan to predict the target of miR‐31a‐5p and found that miR‐31a‐5p could bind to the 3′‐untranslated region (3′UTR) of SATB2 (Figure 3g), a pluripotency transcription factor, which has been previously demonstrated (Deng, Wu et al., 2013; Ge et al., 2015). To further demonstrate whether miR‐31a‐5p regulated osteogenesis via SATB2, the osteogenic capacity of si‐SATB2 treated BMSCs was rejuvenated by miR‐31a‐5p inhibition (Figure 3h,i).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that microRNA‐31a‐5p (miR‐31a‐5p) in BMSCs regulates osteogenic differentiation in tooth eruption via the SATB2 pathway (special AT‐rich binding protein 2; Ge et al., 2015). Our previous results also demonstrated that SATB2 improves the stemness capacity and osteogenic differentiation of aged human BMSCs (Zhou et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, the proliferation rate of DFCs RUNX2+/m showed no difference compared with DFCs RUNX2+/+ in the present study. Previous studies by other researchers reported that RUNX2 mutation showed conflicting role on cell proliferation (Ge et al., ; Li et al., ; Sun et al., ; Wang et al., ; Yan et al., ). We speculated that different cell type and environment among studies might be responsible for the inconsistent results.…”
Section: Discussionmentioning
confidence: 95%
“…Of the currently available 17 studies, five have suggested that miR‐31 was an upstream negative regulator of SATB2 . Furthermore, of the seven known miR‐31 targets, SATB2 was by far the most frequently identified . Physically, miR‐31 was capable of binding to two sites in the SATB2 3′‐UTR region; Figure A demonstrates the sequences that bind with miR‐31 (miRmap: http://mirmap.ezlab.org/).…”
Section: Resultsmentioning
confidence: 99%